2015
DOI: 10.1371/journal.pone.0121903
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a MicroRNA Signature for the Diagnosis of Fibromyalgia

Abstract: BackgroundDiagnosis of fibromyalgia (FM), a chronic musculoskeletal pain syndrome characterized by generalized body pain, hyperalgesia and other functional and emotional comorbidities, is a challenging process hindered by symptom heterogeneity and clinical overlap with other disorders. No objective diagnostic method exists at present. The aim of this study was to identify changes in miRNA expression profiles (miRNome) of these patients for the development of a quantitative diagnostic method of FM. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 51 publications
2
48
0
1
Order By: Relevance
“…On another side, Tam Tam et al, showed that miR-143 expression levels were significantly reduced in DRGs ipsilateral to CFA injection or after nerve damage [84], coinciding with our findings that miR-143 is down regulated in PBMCs of patients of FM suffering of chronic fatigue [16]. This miR, however, has been reported to be upregulated in plasma of CFS/ME patients [19].…”
Section: Mt Impact On the Nervous System And On Pain Reliefsupporting
confidence: 91%
See 3 more Smart Citations
“…On another side, Tam Tam et al, showed that miR-143 expression levels were significantly reduced in DRGs ipsilateral to CFA injection or after nerve damage [84], coinciding with our findings that miR-143 is down regulated in PBMCs of patients of FM suffering of chronic fatigue [16]. This miR, however, has been reported to be upregulated in plasma of CFS/ME patients [19].…”
Section: Mt Impact On the Nervous System And On Pain Reliefsupporting
confidence: 91%
“…Other miRNAs linked to FM and CFS/ME, in particular miR-21 and miR-223, also associate to pain in animal models [16,88,93]. While both miRs are increased in spinal cord after spinal cord injury, the second also increases in the prefontal cortex of the brain in a model of carrageenan induced facial inflammatory pain.…”
Section: Mt Impact On the Nervous System And On Pain Reliefmentioning
confidence: 97%
See 2 more Smart Citations
“…The selection process of these two groups of participants has been previously described by our group. 23 The disease state of the participants, which may in principle seem irrelevant to this study, allowed us to appreciate that our treatments seem valid for samples with low C4a concentrations (below 1000 ng/mL) (FM patients) as well as for samples with higher C4a readings (above 3000 ng/mL) (Controls) (Fig. 5).…”
Section: Heparinized Plasmas Can Be Effectively Analyzed By Elisa Upomentioning
confidence: 97%